Stepwise contraction of the nf Rydberg shells in the 3d photoionization of multiply-charged xenon ions. (28th May 2015) - Schippers, S; A Borovik Jr,; Buhr, T; Hellhund, J; Holste, K; Kilcoyne, A L D; Klumpp, S; Martins, M; Müller, A; Ricz, S; Fritzsche, S
Abstract: Triple photoionization of Xe 3+, Xe 4+ and Xe 5+ ions has been studied in the energy range 670–750 eV, including the 3d ionization threshold. The photon-ion merged-beam technique was used at a synchrotron light source to measure the absolute photoionization cross sections. These cross sections exhibit a progressively larger number of sharp resonances as the ion charge state is increased. This clearly visualizes the re-ordering of the continuum into a regular series of (bound) Rydberg orbitals as the ionic core becomes more attractive. The energies and strengths of the resonances are extracted from the experimental data and are further analysed by relativistic atomic-structure calculations.